PERMASALAHAN DAN RENCANA PENGEMBANGAN KAWASAN PERBATASAN DI PROPINSI KALIMANTAN TIMUR - Drs. M. Tarno Seman, Drs. Sumanto (Jurnal Borneo Administrator, 2005)
The issue on the development of border areas is becoming much more significant in the current decade. Tension between Indonesia and Malaysia on the Ambalat block reminds Central and Provincial Government on the importance of border areas in terms of political (i.e. sovereignty) and economic (i.e. prosperity) development. As a result, the preceding paradigm treating border-areas as ‘backyard’ of the country has been noticeably altered. In order to realize the new paradigm, (border-areas as ‘front yard’), policy readjustments are truly required. In that purpose, this paper tries to explore potential strategies of developing border-areas, particularly through authority and institutional rearrangements as well as action plan implementation.